Knowledge and Attitudes of Pregnant Women towards Bankjo Lamp Technology: Case Study of Choosing a Birth Place - Siswati, Naning; Sunarto, Sunarto; Setiyani, Astuti; Wisnu, Nurwening Tyas (Health Dynamics, 2024)
Background: A high-risk pregnancy jeopardizes both maternal and fetal lives. Despite recommendations for hospital births, six out of ten high-risk expectant mothers in Kawedanan opt for PMB or Community Health Center Maternity. To identify high-risk pregnancies, Kawedanan Community Health Center employs the innovative Bankjo lamp. This study investigates how pregnant women's attitudes and knowledge about Bankjo lamps influence their maternity location choice. Methods: This type of research uses quantitative descriptive research. This observational analytical research involved 57 expectant mothers due to maternity in January, February, or March. Using a cross-sectional design, the study treated knowledge and attitudes about Bankjo lamps as independent variables, with maternity location preference as the dependent variable. Data collection methods included knowledge and attitude questionnaires and monthly midwife reports. The data was analyzed using the Chi-Square test and descriptive statistics in the form of frequency distribution with presentation. Results: Findings indicate that pregnant women generally possess adequate knowledge about suitable maternity locations, with some showing insufficient understanding. A significant correlation (p = 0.013) exists between knowledge levels and preferred birthplace. Despite the preference for hospital births among nearly all expectant mothers, a majority hold negative attitudes, strongly correlated (p = 0.000) with their birthplace choices. Interestingly, while most pregnant women understand the Bankjo lamp innovation well, they harbor negative attitudes toward it. Nevertheless, almost all opt for hospital births, prioritizing medical safety despite reservations about new technologies. Conclusions: The study underscores the need for government support in advancing maternal health initiatives, including innovative technologies like Bankjo lamps. Enhancing awareness and promoting positive attitudes among expectant mothers can foster safer childbirth practices. By disseminating knowledge and addressing misconceptions, healthcare providers can better support high-risk pregnancies, ensuring better outcomes for both mothers and babies.